Beyond symptom control for attention‐deficit hyperactivity disorder (ADHD): what can parents do to improve outcomes?. (9th June 2014) - Tarver, J.; Daley, D.; Sayal, K.
Abstract Attention‐deficit hyperactivity disorder (ADHD) and its associated behavioural manifestations develop and progress as the result of complex gene‐environment interactions. Parents exert a substantial influence and play a major role in their child's social environment. Despite this, recent evidence has suggested that adapting the child's environment via parenting interventions has minimal effects on child ADHD symptoms when analysing data from informants who are probably blind to treatment allocation. However, adverse parenting and family environments may act as a source of environmental risk for a number of child outcomes beyond ADHD symptoms. This is a narrative review that critically discusses whether parenting interventions are beneficial for alternative functioning outcomes in ADHD including neuropsychological, academic and social functioning and disruptive behaviour and how parenting and familial environments may be associated with these outcomes. In addition, the review explores how parental depression and parenting efficacy impact on capacity for optimal parenting and whether parenting interventions benefit parents too. A review of the evidence suggests that with modification, parenting interventions are beneficial for a number of outcomes other than ADHD symptom reduction. Improving the parent–child relationship may have indirect benefits for disruptive behaviour. Furthermore, parenting behaviours may directly benefit child neuropsychological, academic and social functioning. Parenting interventions can have therapeutic benefits for parents as well as children, which is important as parent and child well‐being is likely to have a transactional relationship. Evaluation of the clinical success of parenting interventions should focus on a wider range of outcomes in order to aid understanding of the multifaceted benefits that they may be able to offer. Parenting interventions should not be seen as a redundant adjunct to medication in multi‐modal treatment approaches for ADHD; they have the potential to target outcomes that, at present, medication seems less able to improve.